EVALUATION OF BIOLOGICAL ACTIVITIES OF THE ESSENTIAL OIL AND MAJOR COMPONENT OF SYZYGIUM AROMATICUM - A. Saeed; D. Shahwar (Journal of Animal and Plant Sciences, 2015)
Hydro distilled essential oil from buds of Syzygium aromaticum was investigated for antioxidant and enzyme inhibition activities. GC-MS analysis of the oil indicated eugenol (80.0%) as the major constituent followed by caryophyllene (10.27%) and eugenol acetate (5.03%). Thin layer chromatography of the essential oil yielded eugenol confirmed by comparison of spectral data (EI-MS, 1H and 13C-NMR) with the literature. Reactive oxygen species (ROS), xanthine oxidase (XO), acetylcholine esterase (AChE) inhibition, lipid peroxidation by thiobarbituric acid (TBA) and ferric thiocyanate (FTC) methods, 1,1-diphenyl-2-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays were carried out on the essential oil and the major component. The IC50 values for eugenol showed significant potential against enzyme inhibition and antioxidant activities while the essential oil of S. aromaticum was found moderately active.
Keywords: Syzigium aromaticum; essential oil; eugenol; ROS; xanthine oxidase; acetylcholine esterase